2005
DOI: 10.1016/j.jmhg.2005.10.012
|View full text |Cite
|
Sign up to set email alerts
|

The ‘other half’ of breast cancer: A review of male breast cancer

Abstract: Male breast cancer has always been shadowed by the attention received by its other half of the coin; female breast cancer. It is widely known to be 1% of all breast cancer, constituting also about 1% of all breast cancer literature. As a rare disease, it is fortunate that its female counterpart has provided it with the wealth of knowledge to treat it effectively. Although very similar, male breast cancer has unique characteristics requiring a different approach to female breast cancer. In this review, the caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 88 publications
1
6
0
2
Order By: Relevance
“…Because of the high sensitivity to oestrogen in male breast tumours, a large proportion of MBC patients have a good response to hormonal treatment [1] [125]. Historically, orchiectomy, adrenalectomy and hypophysectomy have also been useful surgical methods for the treatment of male breast tumours [126] by altering the hormonal state of the male body [127], but today Tamoxifen is accepted as a standard adjuvant hormonal therapy for hormone-sensitive breast cancer [13] [92] [128], which has been shown to produce results comparable with orchiectomy [129] and with high levels of patient acceptance [7]. Several retrospective studies have shown good results with adjuvant Tamoxifen, resulting in improved five-year overall survival and/or fiveyear disease-free survival [78] [131], but there are a few retrospective studies questioning Tamoxifen treatment of MBC [10] [132]- [134].…”
Section: Hormone Treatmentmentioning
confidence: 99%
“…Because of the high sensitivity to oestrogen in male breast tumours, a large proportion of MBC patients have a good response to hormonal treatment [1] [125]. Historically, orchiectomy, adrenalectomy and hypophysectomy have also been useful surgical methods for the treatment of male breast tumours [126] by altering the hormonal state of the male body [127], but today Tamoxifen is accepted as a standard adjuvant hormonal therapy for hormone-sensitive breast cancer [13] [92] [128], which has been shown to produce results comparable with orchiectomy [129] and with high levels of patient acceptance [7]. Several retrospective studies have shown good results with adjuvant Tamoxifen, resulting in improved five-year overall survival and/or fiveyear disease-free survival [78] [131], but there are a few retrospective studies questioning Tamoxifen treatment of MBC [10] [132]- [134].…”
Section: Hormone Treatmentmentioning
confidence: 99%
“…Globally, breast cancer makes up about 22.9% of all cancers in women and therefore is an important concern for all women (Lakshmi, Raju Athira, Teena, & Vijayalakshmi, 2012). It is documented that about 1% of men globally also develop breast cancer (Ying, Agrawal, & Cheung, 2005). This makes issues about breast cancer a concern for humanity.…”
mentioning
confidence: 99%
“…The result of the studies of immunohistochemistry coincides with the reviewed literature, these highly endocrine tumours being responsive without overexpression of the HER-2 [23, 24]. Neither a family history of this pathology nor other risk factors associated with the disease were collected, so this is considered a sporadic and unusual case.…”
Section: Discussionsupporting
confidence: 67%